Improving students’ metacognitive abilities and creative thinking skills through STEM-based in online learning - Retno Wilis; Baskoro Adi Prayitno; Widha Sunarno; Suwanida Anjirawaroj (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Creative thinking skills are crucial to current generations dealing with 21st-century challenges. However, studies on higher-order thinking skills remain limited. CTS can be easily empowered if students have good metacognitive abilities. This study analysed the effect of STEM-based online learning lesson plans on the CTS of students and metacognitive abilities on the inheritance of living things through online learning. The pretest-posttest research designs with a non-equivalent control group were used. The treatment given in the experimental class was the implementation of a STEM-based online learning lesson plan, while the control class was taught through traditional methods used by the teachers. The results of this study indicated that the CTS and metacognitive abilities of students in the experimental class were significantly higher than that of the control class [F(1,54) = 105.287, p = 0.000 and F(1,54) = 103.943, p = 0.000, respectively]. In conclusion, the STEM-based online learning lesson plan is effective in improving the CTS and metacognitive abilities of students.